Pengaruh Literasi Keuangan, Gaya Hidup dan Lingkungan Sosial Terhadap Perilaku Keuangan Mahasiswa: Pengaruh Literasi Keuangan, Gaya Hidup dan Lingkungan Sosial Terhadap Perilaku Keuangan Mahasiswa - Suyanto; Yohanes Maria Vianey Kenale Sada (Jurnal Literasi Akuntansi, 2022)
Purpose: This study aims to determine whether the influence of financial literacy, lifestyle and social environment. This study examines whether the influence of financial literacy, lifestyle and social environment on the financial behavior of students. Method: The population in this study were active undergraduate students who were studying at the Faculty of Economics, Universitas Sarjanawiyata Tamansiswa Yogyakarta. The sample in this study were students of the accounting and management study program who were studying at the Faculty of Economics, Universitas Sarjanawiyata Tamansiswa Yogyakarta. The sample obtained was 108 respondents with the snowball sampling method. This data was analyzed using multiple linear analysis with the help of IBM SPSS. Finding: The results of the study prove that financial literacy have a positive effect on financial behavior, lifestyle have a positive effect on financial behavior, and the social environment have a positive effect on financial behavior. Keyword: Financial Literacy, Lifestyle, Social Environment, Student Financial Behavior